A spectral approach for time-fractional diffusion and subdiffusion equations in a large interval - Dehestani, Haniye; Ordokhani, Yadollah; Razzaghi, Mohsen (Mathematical Modelling and Analysis, 2022)
In this paper, we concentrate on a class of time-fractional diffusion and subdiffusion equations. To solve the mentioned problems, we construct twodimensional Genocchi-fractional Laguerre functions (G-FLFs). Then, the pseudooperational matrices are used to convert the proposed equations to systems of algebraic equations. The properties of pseudo-operational matrices have reflected well in the process of the numerical technique and create an approximate solution with high precision. Finally, several examples are presented to illustrate the accuracy and effectiveness of the technique.